Nonlinear Effects of Dusty Plasmas using Homogenous Nonequilibrium Molecular Dynamics Simulations - Shahzad, Aamir; He, Mao-Gang (Journal of Applied Nonlinear Dynamics, 2026)
Three-dimensional strongly coupled complex (dusty) plasma (SCCDP) is modeled using homogenous nonequilibrium molecular dynamics (HNEMD) simulations. The thermal conductivity (λ0) and the effects of external force field (F*) strength on the λ0 of SCCDP are calculated at higher screening strengths (κ) from generalized Evan’s algorithm. It has been shown that the presented investigations exhibit a non-Newtonian effect that the λ0(Γ) increases with increasing force field strength that represents interaction contributions in Yukawa conductivity. It is also verified that the results obtained with different external force filed strengths are in satisfactory agreement with earlier numerical results and with reference set of data showed deviations within less than ± 10% for most of the present data point. Our very recently computed thermal conductivity at lower κ is validated by comparing the results of λ0(Γ) at higher κ that also extended the range of force field strength (0.001≤F*≤ 0.1) which explains the nature of nonlinearity of SCCDP.